Reinterpretasi : Motif Pucuak Rabuang pada Media Teko - Heru Ningrum; Dharsono Dharsono; Wilma Sriwulan (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
AbstractThe creation of ceramic craft motifs of pucuak rabuang motif is a reinterpretation of the philosophy of the Minangkabau tradition